PENGARUH PENERAPAN STANDAR AKUNTANSI P EMERINTAHAN DAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN SKPD KABUPATEN SIGI - Nurpaida, Andi (Katalogis, 2017)
The study intends to determine the influence of the aplication of governmental accounting standars and internal audit on the quality of financial statement of governmental working units (SKPD) in Sigi District .It is a quantitative study with survey approach to answer hypotheses with statistical technique with the test conducted on 27 units of local government units by selecting 54 respondents consisting of budget users and officials of financial administration in SKPD of Sigi District. Data Collected by questionnaires. The result finds that the aplication of government accounting standards and internal audit simultaneously and partially have positive and significant influence on the quality of financial statementsÂ  of SKPD Sigi. This means that when the government accounting standards and internal audit applied well, then the quality of the fincancial statements will also be better.